Estimating the future global dose demand for measles–rubella microarray patches - Ko, Melissa; Malvolti, Stefano; Cherian, Thomas; Mantel, Carsten; Biellik, Robin; Jarrahian, Courtney; Menozzi-Arnaud, Marion; Amorij, Jean-Pierre; Christiansen, Hans; Papania, Mark J.; Meltzer, Martin I.; Masresha, Balcha Girma; et al. (Frontiers in Public Health, 2023)
Background Progress toward measles and rubella (MR) elimination has stagnated as countries are unable to reach the required 95% vaccine coverage. Microarray patches (MAPs) are anticipated to offer significant programmatic advantages to needle and syringe (N/S) presentation and increase MR vaccination coverage. A demand forecast analysis of the programmatic doses required (PDR) could accelerate MR-MAP development by informing the size and return of the investment required to manufacture MAPs. Methods Unconstrained global MR-MAP demand for 2030–2040 was estimated for three scenarios, for groups of countries with similar characteristics (archetypes), and four types of uses of MR-MAPs (use cases). The base scenario 1 assumed that MR-MAPs would replace a share of MR doses delivered by N/S, and that MAPs can reach a proportion of previously unimmunised populations. Scenario 2 assumed that MR-MAPs would be piloted in selected countries in each region of the World Health Organization (WHO); and scenario 3 explored introduction of MR-MAPs earlier in countries with the lowest measles vaccine coverage and highest MR disease burden. We conducted sensitivity analyses to measure the impact of data uncertainty. Results For the base scenario (1), the estimated global PDR for MR-MAPs was forecasted at 30 million doses in 2030 and increased to 220 million doses by 2040. Compared to scenario 1, scenario 2 resulted in an overall decrease in PDR of 18%, and scenario 3 resulted in a 21% increase in PDR between 2030 and 2040. Sensitivity analyses revealed that assumptions around the anticipated reach or coverage of MR-MAPs, particularly in the hard-to-reach and MOV populations, and the market penetration of MR-MAPs significantly impacted the estimated PDR. Conclusions Significant demand is expected for MR-MAPs between 2030 and 2040, however, efforts are required to address remaining data quality, uncertainties and gaps that underpin the assumptions in this analysis.